Urban Design - Saunders, William S.; Krieger, Alex, 1951- (Book collections on Project MUSE., 2009)
Fifty years ago a landmark conference at Harvard University established urban design as a distinct architectural and planning practice. Today, with the world's urban population surpassing three billion people, urban design has become more crucial than ever. Indeed, the concerns that initially brought leading architects and city planners together--including concerns over sprawl, pollution, and aging infrastructure--have only intensified over the past half century. In Urban Design, Alex Krieger and William S. Saunders have assembled prominent figures in architecture, planning, and landscape design.